Clustering of date palm (Phoenix dactylifera L.) cultivars using morphological and yield attributes as selection criteria - Naseer, Mehwish; Fatima, Sana; Hameed, Mansoor; Basharat, Sana; Parveen, Zahida; Ahmad, Muhammad Sajid Aqeel; Ahmad, Farooq; Asghar, Ansa; Rani, Wasifa; Shafqat, Jazab; Shah, Syed Mohsan Raza (International Journal of Applied and Experimental Biology, 2026)
Thirty-two (32) date palm (Phoenix dactylifera L.) cultivars of diverse origin were characterized morphologically to assess the extent of inter-cultivar variability. These cultivars originated in parts of Pakistan, Iran, Iraq, and Saudi Arabia. A great magnitude of inter-cultivar variation was found in the set of date palm cultivars, not only in quantitative, but also in qualitative morphological characteristics. A multivariate (cluster) analysis of the date palm cultivars showed a lesser degree of similarity in qualitative morphological characters as compared to quantitative morphological characters. Based on qualitative morphological characters of the trunk and leaves, most of the cultivars from Punjab and two from Baluchistan were closely similar to each other, and a similar pattern of similarity was noted in their quantitative morphological characteristics. Characteristics like color of spines, number of leaflets per leaf, and size, shape, and color of fruits and seeds were found to be suitable morphological selection criteria for the exact identification of date palm cultivars. Date palm cultivars Dakki (from Khyber Pakhtunkhwa) and Chawara (from Baluchistan), and Hallawi-I (from Iraq) ranked better regarding fruit size, weight, and taste quality. Khudrawi (from Iraq) and Saib (from Punjab) were also likable, having large and tasty fruits.